Cossura yacy sp. nov. (Cossuridae, Annelida) from a tropical Brazilian estuary - Sousa,Lorena K. S. (2019)
ABSTRACT The family Cossuridae is monogeneric for Cossura Webster & Benedict, 1887 which currently has 28 known species, three of which already recorded for Brazilian coast. In the present study we describe Cossura yacy sp. nov. increasing to 29 the number of known Cossuridae species. We have found and analyzed 60 individuals of C. yacy sp. nov. from São Marcos estuarine complex (ca. 02°S; 44°W) around São Luís Harbor (Maranhão, Brazil). It differs from other species of genus also by the presence of the two pairs of nuchal organs at lateral margins of the peristomium, branchial filament in the median region of the third chaetiger and by short and long capillary smooth chaetae with spinulosa on the distal half. These two chaetal types are present through the body both in the neuropodia and in the notopodia. Adults specimens of the Cossura yacy sp. nov. have seven notopodial and five neuropodial chaetae in the 5th parapodium; nine notopodial and seven neuropodial chaetae in the 20th parapodium; five notopodial and six neuropodial chaetae in the 43th parapodium. Pygidium has three long anal cirri, reaching the fourth posterior segment.